Structural shear performance of insulated precast concrete sandwich panels with steel plate connectors. (15th July 2020) - Kinnane, Oliver; West, Roger; Hegarty, Richard O.
Highlights: Large experimental study analyses the shear performance of precast sandwich panels with steel plate connectors. Connectors of varied thickness and depth give rise to different load capacities, stiffnesses and failure modes. The insulation layer plays a significant role in preventing rotation in response to a shear load. Finite element analysis is undertaken and identifies significant nonlinear behavior in the panel response. Abstract: Precast concrete sandwich panels are an increasingly popular means of building cladding. They can be designed with high thermal resistance by embedding abundant insulation between two concrete wythes. Steel, in the form of thin plate connectors, remains one of the most common tie materials to support the outer wythe of concrete vertically, and transmit lateral forces from the external rain-screen to the internal structural wythe. The optimum design of steel shear connectors must satisfy thermal and strength capacity constraints. An extensive experimental study analyses the structural shear performance of precast concrete sandwich panels with steel plate connectors of various dimensions that give rise to different load capacities, stiffnesses and failure modes.